The Material Imperialism of the Home in Paule Marshall’s The Chosen Place, The Timeless People - Bartell, Brian (Journal of Literary Studies, 2020)
“The Material Imperialism of the Home” in Paule Marshall’s The Chosen Place, The Timeless People argues that in the fictional Caribbean country Bourne Island, where this novel about post-World War II development is set, home is understood as a conflicted site of technological and material structures left over from slavery and colonialism. It further focuses on the novel’s narration of how global transformations in the economy and the development of new technological ideologies that were connected to histories of slavery and processes of racialisation emerged not just in imperial centres, but also in the quotidian places of the Caribbean home. The first part of the article considers the different ways that the “Timeless People” and protagonist Merle Kinbona experience home as an entanglement with the colonial and slave past, and how this condition affects their potential futures. The second half of the article looks at the novel’s treatment of cybernetic and information technologies through the character of white anthropologist Allen Fuso and how his efforts to resist becoming a United States-based domestic, heteronormative, “IBM Machine” are related to histories of racial oppression, technology, imperialism, and new forms of value extraction. Opsomming “The Material Imperialism of the Home” in Paule Marshall se The Chosen Place, The Timeless People voer aan dat in die fiktiewe Karibiese land Bourne Island, waar hierdie roman oor ontwikkeling ná die Tweede Wêreldoorlog afspeel, die tuiste verstaan word as 'n plek wat deur konflik gekenmerk word; met tegnologiese en materiële strukture wat oorgebly het van slawerny en kolonialisme. Dit fokus verder op die roman se vertelling van hoe globale transformasies in die ekonomie en die ontwikkeling van nuwe tegnologiese ideologieë wat met geskiedenisse van slawerny en prosesse van etnisering verband gehou het, nie net in imperiale sentrums plaasgevind het nie, maar ook in die daaglikse plekke van die Karibiese tuiste. Die eerste deel van die artikel bestudeer die verskillende maniere waarop die “Tydlose Mense” en protagonis Merle Kinbona “huis” ervaar as ineengestrengel met die koloniale en slawernyverlede, en hoe hierdie toestand hul potensiële toekomste beïnvloed. Die tweede helfte van die artikel fokus op die roman se hantering van kubernetiese en inligtingstegnologieë deur die karakter van die wit antropoloog Allen Fuso, en hoe sy pogings om daarteen weerstand te bied om 'n Verenigde State-gebaseerde huislike, heteronormatiewe “IBM-masjien” te word, verband hou met geskiedenisse van rasse-onderdrukking, tegnologie, imperialisme, en nuwe vorme van waarde-ontginning.